Concepção, modelagem, simulação e usinagem de um aerofólio automotivo auxiliado por computador - Rocha, Marcelo Ricardo [UNESP]; Jurisato, Augusto Seolin [UNESP]; Hellmeister, Luiz Antonio Vasques [UNESP] (My University, 2013)
With the advancement of computer technology and the availability of technology computer aided design (CAD) errors in the designs are getting smaller. To this end the project aims to assess the reliability of the machine (CNC), which was designed by students of mechanical engineering college engineering - UNESP Bauru, by designing, modeling, simulation and machining an airfoil automotive. The profile template selected for the study will be a NACA 0012 machined plates in medium density fiberboard (MDF) and will be performed with a structural analysis simulation using finite elements and a software CFD (Computational Fluid Dynamics), and test the real scale model in a wind tunnel. The results obtained in the wind tunnel and CFD software will be compared to see the error in the machining process.
Keywords: CAD; CAM; CFD; CNC; Rear wing